Honey-pot effect on pedestrian attention to public displays in a virtual environment: head turns, walking past, and direct approaches - Kuratomo, Noko; Kray, Christian; Zempo, Keiichi (Frontiers in Virtual Reality, 2025)
IntroductionObservers in public display environments often follow the gaze and body orientation of nearby pedestrians—a phenomenon termed the “honey-pot effect”—thereby increasing overall attention to the screen. While prior research has demonstrated this effect for interactive installations, its applicability to passive, non-interactive content and its impact on subsequent content recognition remain unexplored. This study employed a virtual-reality simulation of an urban sidewalk, featuring a moving avatar and a stationary digital display, to investigate whether simple head-and-body orientations by one pedestrian can direct attention and enhance content awareness among following pedestrians.MethodsWe conducted an experiment where an avatar walked behind another avatar passing in front of public display on a virtual sidewalk. The avatar’s behavior was set to three conditions: Walking past, Attention, and Approach to the public display.ResultsThe results of the experiment with 18 participants showed that participants were more likely to turn and look at the display influenced by the avatar in front approached and stopped in front of the display. Likewise, when a pedestrian approaching from the opposite direction—whose face was visible—turned toward the display, participants were similarly more inclined to turn and look. However, no effect was observed on participants’ recognition of the content. Among the participants, which included eight Germans and eight Japanese, there was no difference in how easily the reaction to the behavior of other pedestrians occurred.DiscussionsThese findings suggest that, even for static display content, attracting the “first pedestrian“ through visually striking designs or the use of sound can be critical. Besides, it is important not only to consider display content but also to take into account pedestrian walking directions when placing displays, so that more people will be encouraged to notice and view the content.